Insulin resistance is associated with preclinical carotid atherosclerosis in patients with type 1 diabetes. Issue 7 (7th April 2020) - Pané, Adriana; Conget, Ignacio; Boswell, Laura; Ruiz, Sabina; Viñals, Clara; Perea, Verónica; Giménez, Marga; Cofán, Montserrat; Blanco, Jesús; Vinagre, Irene; Esmatjes, Enric; Ortega, Emilio; et al.
Abstract: Aim: Although insulin resistance (IR) is a growing trait among type 1 diabetes (T1D) population, its relationship with atherosclerosis has been scarcely studied. We assessed the association between IR indexes and carotid atherosclerosis in T1D, a population at high cardiovascular disease (CVD) risk. Materials and Methods: We evaluated 191 participants with T1D and no prior CVD with at least one of the following criteria: ≥40 years old; diabetic nephropathy; or T1D duration ≥10 years harbouring ≥1 additional CVD risk factor. IR was assessed with the metabolic syndrome (MetS) harmonized definition proposed in 2009 and the estimated glucose disposal rate (eGDR), a T1D‐specific IR surrogate marker (lower values indicating higher IR). Standardized carotid ultrasonography was performed, recording intima‐media thickness (IMT), plaque presence and maximum height of plaque. Comparisons between patients according to their MetS status as well as concerning eGDR values were performed. Results: The participants' median age was 47.4 (41.1‐53.3) years and diabetes duration 25.7 (21.6‐32.5) years. Plaque prevalence was higher in patients with greater IR (49.1%, 29.1% and 20%, P = .001, for any plaque according to decreasing eGDR tertiles). Conversely, no statistically significant higher plaque prevalence was found in participants with MetS. In multivariate analyses (adjusted for general‐ and T1D‐specific risk factors, and statin treatment), MetS was associated with neither IMT nor plaque. On the contrary, eGDR was independently related to ≥2 plaques ( P = .018) and maximum plaque height ( P  < .01). Conclusions: In T1D, IR assessed through eGDR but not by MetS definition was independently associated with plaque burden, a predictor of CVD.